A Smart Home Management based on M2M/IoT Technologies - Djehaiche, Rania; Aidel, Salih; Benhamimid, Karima (University of Eloued جامعة الوادي, 2022)
The advances in the applications based on Machine-to-machine (M2M) and Internet of Things (IoT) enabled the evolution of Smart home solutions wirelessly. This paper aims to present the implementation of smart homes based on M2M/IoT technologies using wireless sensor networks (WSNs). In this system, Arduino Uno microcontroller has been used with several compatible sensors, actuators, and modules to make the control and take the suitable decision. In addition, various technologies of communication such as Bluetooth, Wi-Fi, Ethernet, and GSM are used as wireless communication mediums to enable the interaction between users and the proposed system. Our Smart home implements integrated functions and services like security, indoor care, and outdoor care. A simple smartphone remotely controls these functions through our mobile application named ‘Raniso’. The experimental results of using the proposed system show that a variety of events can be detected and monitored efficiently. Gas leakage, fire, and housebreaking situations can be detected and users get notified about them via Calls and messages. Also, lights, temperature monitoring, and fans can be easily controlled remotely. Besides, the proposed system can perform some proper actions including decreasing gas concentration via the opening of windows, watering the garden when the soil is dry, saving the rainwater, and so on. Our smart home system is very utile to prevent losses in resources and human life caused by undesired events as also it conserves energy and provides comfort.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Smart home, M2M, IoT, WSNs, Mobile Application